Sistem Informasi Perhitungan Stok Barang Per Gudang pada PT.Dima Habadi Menggunakan Metode Double Exponential Smoothing - Nurul Hilda Syani Putri; Suhendi Suhendi; Imron Nugraha Imron Nugraha (Jurnal Bangkit Indonesia, 2019)
This research focused on the problems in the sense of recording transactions on PT.DIMA HABADI who still have problems in stock reporting while doing the recording of transactions very much. Stock reporting process that still requires a long time, because the manual recording of transactions and should crosscheck back relatively much. Thus the purpose of this research cope in order to improve the weaknesses recording manually, and also to facilitate the stocking statements. The method used is the study of literature and data collection through in-depth interviews and direct observation to examine the workings of recording the transaction in progress. System development methodology is the use of "Waterfall Model" and is implemented through the programming language Visual Studio 2013 and SQL Server 2012 as the database.